HYBRID LEADERSHIP IN MULTICULTURAL CONTEXTS: A SYSTEMATIC LITERATURE REVIEW - de Souza Pereira, Maxwell (Humanas em Perspectiva, 2026)
The growing complexity of the global organizational environment poses unprecedented challenges to contemporary leadership, particularly regarding the management of geographically distributed and culturally diverse teams. This article presents a systematic literature review on the concept of hybrid leadership — defined as a leader’s capacity to integrate in-person and remote leadership competencies within multicultural environments — with the aim of mapping the state of the art, identifying theoretical gaps, and proposing a future research agenda. Following PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), 78 articles published between 2015 and 2024, indexed in Web of Science, Scopus, and SciELO databases, were analyzed. Results demonstrate that effective hybrid leadership in multicultural contexts requires: (a) high cultural intelligence; (b) adaptive flexibility; (c) mastery of asynchronous communication tools; and (d) sensitivity to Hofstede’s power distance and individualism-collectivism dimensions. Furthermore, a convergence is observed among transformational leadership, servant leadership, and ambidextrous leadership as theoretical pillars of intercultural hybrid leadership. This research contributes to the field by consolidating scattered empirical evidence and offering a preliminary integrative model. Methodological gaps and practical recommendations for managers and multinational organizations are discussed.